2021
DOI: 10.1002/chem.202102204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Entropy‐Driven Inhibition of Dipeptidyl Peptidase III by Hydroxyethylene Transition‐State Peptidomimetics

Abstract: Dipeptidyl peptidase III (DPP3) is a ubiquitously expressed Zn-dependent protease, which plays an important role in regulating endogenous peptide hormones, such as enkephalins or angiotensins. In previous biophysical studies, it could be shown that substrate binding is driven by a large entropic contribution due to the release of water molecules from the closing binding cleft. Here, the design, synthesis and biophysical characterization of peptidomimetic inhibitors is reported, using for the first time an hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Both SHE and HER inhibited the enzyme with an IC 50 of 98.5 µM and 13.8 µM, respectively. As for tynorphin, an endothermic binding to human DPP III was observed with K d values of 23 µM for SHE and 11 µM for the binding of HER [54]. The solved crystal structure of the complex SHE-human DPP III (E451A) revealed almost the same binding mode of this pseudopentapeptide inhibitor as that of tynorphin [13].…”
Section: Peptidomimetic Inhibitorsmentioning
confidence: 83%
See 1 more Smart Citation
“…Both SHE and HER inhibited the enzyme with an IC 50 of 98.5 µM and 13.8 µM, respectively. As for tynorphin, an endothermic binding to human DPP III was observed with K d values of 23 µM for SHE and 11 µM for the binding of HER [54]. The solved crystal structure of the complex SHE-human DPP III (E451A) revealed almost the same binding mode of this pseudopentapeptide inhibitor as that of tynorphin [13].…”
Section: Peptidomimetic Inhibitorsmentioning
confidence: 83%
“…Only recently, by using the knowledge of 3-D structure of complex tynorphin-inactive human DPP III, Ivković et al [54] designed peptidomimetic inhibitors. They synthesized (S)-and (R)-epimers of hydroxyethylene transition state mimetics of tynorphin, named SHE and HER (Figure 7), and characterized their potentials as inhibitors of human DPP III.…”
Section: Peptidomimetic Inhibitorsmentioning
confidence: 99%
“…The latest approach to generate specific DPP3 inhibitors is the design of pseudopeptides. Ivokovic et al [82] described the synthesis of two epimers that feature the main tynorphin scaffold, where the scissile peptide bond is replaced by non‐cleavable hydroxyethylene isostere. Both, the ( S )‐ and the ( R )‐epimer (named SHE and HER, respectively) inhibit hDPP3 in vitro (Table 3) and HER was additionally shown not to be degraded by the enzyme over a period of 24 h [82].…”
Section: Substrates and Inhibitorsmentioning
confidence: 99%
“…In summary, DPP3 has emerged as a valuable biomarker to predict the severety of shock syndromes, and importantly, lends itself as an attractive target to attenuate the potentially lethal symptoms. In that context, DPP3 activity could be reduced either by bioceuticals, e.g., antibodies directed against the protein or small molecule inhibitors, as described recently [82].…”
Section: Involvement In Pathophysiological Processesmentioning
confidence: 99%
“…While Li et al ( 88 ) demonstrated that increased enkephalin in the rostral ventrolateral medulla after electro acupuncture decreases blood pressure. N terminal of both enkephalin are anchored to DPP3 via hydrogen bonding and electrostatic interactions of the tyrosine-318, glutamate-316, and asparagine-394 side chains and cleaved by DPP3 ( 89 ). Furthermore, leucine-enkephalin binds to inactive DPP3 isoform, but the difference in the C-terminal residue between the two structures of enkephalin is not significant.…”
Section: Biological Propertiesmentioning
confidence: 99%